2021
DOI: 10.1111/gcb.15906
|View full text |Cite
|
Sign up to set email alerts
|

Net effects of conservation agriculture principles on sustainable land use: A synthesis

Abstract: Conservation agriculture represents a combination of three agronomic principles, including no-tillage or reduced tillage, permanent residue retention, and crop rotation (Palm et al., 2014). As the central and original principle, no-tillage soil management is commonly associated with three benefits for agriculture, soil, and climate: improved crop production, soil and water conservation, and increased

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Tillage reduction, including no tillage or reduced tillage, represents another kind of important conservation practice that was first invented in 1930s for wind erosion control (Goudie & Middleton, 1992). Tillage reduction has been widely adopted, because these practices can increase soil resistance by promoting soil compaction, crust formation, and SOC accumulation (Xiao, Kuhn, et al, 2021). Conservation practices that can increase soil stability, such as no tillage and soil stabilizer application, may also limit the saltation process, either by increasing the crust strength or by increasing the stability to resist the impacts of saltating particles (Armbrust, 1999; Gomes et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Tillage reduction, including no tillage or reduced tillage, represents another kind of important conservation practice that was first invented in 1930s for wind erosion control (Goudie & Middleton, 1992). Tillage reduction has been widely adopted, because these practices can increase soil resistance by promoting soil compaction, crust formation, and SOC accumulation (Xiao, Kuhn, et al, 2021). Conservation practices that can increase soil stability, such as no tillage and soil stabilizer application, may also limit the saltation process, either by increasing the crust strength or by increasing the stability to resist the impacts of saltating particles (Armbrust, 1999; Gomes et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, one previous study observed that increasing crop yield in CA may be influenced by the improve soil fertility by conserving soil and water and sequestering organic carbon in farmed soils, hence lowering extremes of waterlogging and drought [25] . Furthermore, the higher production in CA might be related to improved soil struc- ture and stability, which would allow for better drainage and water holding capacity [26] .…”
Section: Discussionmentioning
confidence: 99%
“…CAP support for sustainable agricultural practices is limited and unable to counteract the damaging impact of e.g., hectarebased income support with its weak environmental requirements. This is unfortunate as sustainable agricultural practices can support soil protection and soil biodiversity and thereby contribute to close nutrient cycles, and benefit climate and biodiversity (Jian et al, 2020;Köninger et al, 2021;Redlich et al, 2021;Xiao et al, 2021b). In doing so, these practices could support achieving the Farm to Fork objective and global environmental goals.…”
Section: Limited Support For Sustainable Agricultural Practicesmentioning
confidence: 99%